GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 652 species occurrences available in GBIF matching the query: TaxonKey: Marsilea strigosa Willd.. The dataset includes 652 records from 48 constituent datasets: 1 records from Phanerogamic Botanical Collections (S). 6 records from SysTax - Botanical Gardens. 1 records from Rio de Janeiro Botanical Garden Herbarium Collection. 1 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 38 records from Inventario Español de Especies Terrestres (MAGRAMA). 46 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 9 records from Instituto Pirenaico de Ecología-CSIC: Herbarium JACA. 2 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 83 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 1 records from Carnet en Ligne. 3 records from Herbarium of Namur. 1 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 8 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 4 records from Phytochorologie des départements français. 1 records from Herbario de la Universidad de Sevilla, SEV. 4 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 2 records from Universitat de Girona: HGI-Cormophyta. 1 records from Herbarium specimens, Harmas J.H. Fabre (FABR - Sérignan-du-Comtat) of the Muséum national d'Histoire naturelle (MNHN - Paris). 3 records from Instituto Nacional de Pesquisas da Amazônia (INPA) - Herbarium. 110 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 2 records from CIBIO, Alicante:ABH-GBIF. 3 records from SANT herbarium vascular plants collection. 14 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 16 records from Natural History Museum (London) Collection Specimens. 2 records from Institut Botanic de Barcelona, BC. 2 records from GBIF-PORTUGAL-Herbário João de Carvalho e Vasconcellos, I.S.A./U.T.L.. 7 records from Actualisation de la cartographie des Ptéridophytes de France et d'Europe occidentale. 1 records from Institut Menorquí d'Estudis. Colección Histórica de Rodríguez Femenías, Herbarium Generale Minoricae: HGM-Femenias. 4 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 1 records from Jardín Botánico Atlántico, Gijón: JBAG-Laínz. 9 records from Universidad de Málaga: MGC-Cormof. 1 records from Herbarium of The New York Botanical Garden. 21 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 1 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Herbario COFC). Facultad de Ciencias. Universidad de Córdoba. 1 records from Marie-Victorin Herbarium (MT). 4 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 1 records from Harvard University Herbaria. 1 records from Hortus Botanicus Sollerensis Herbarium (FBonafè). 2 records from Herbarium Berolinense. 4 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 1 records from Herbier A. Le Grand (BOUM). 42 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 2 records from Herbario de la Universidad de Granada: GDA. 29 records from Inventaire National du Patrimoine Naturel : CBN Méditerranéen de Porquerolles. 148 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 5 records from Inventaire National du Patrimoine Naturel : Espèces Végétales Menacées de France métropolitaine. 2 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 1 records from Jardín Botánico de Córdoba: Herbarium COA.
Keywords: GBIF; biodiversity; species occurrences